A study on bottlenecks in adoption of broiler farming in south – western Punjab (Indian Journal of Animal Production and Management, 2024)
A survey work was designed to study the present management status, impact of farm sizes on adoptability  of various recommended practices and major bottlenecks faced by broiler farmers in adoption of broiler  farms in Mansa and Sangrur districts of Punjab. To undertake this survey work, total 70 broiler farmers  were selected for the collection of data. Analysis of data revealed that 60.00% farmers expressed their  views regarding the high cost and poor quality of inputs including costs of day-old-chicks, constructional  material, feed, medicines and equipments. Out of 70 farmers, 82.85% farmers also complained about non availability of loan including rigid procedure for supply of loans and 24.28% farmers also complained about  high cost of electricity. Overall 48.60% farmers faced the problem of oligopsony marketing structure for  purchase of quality-day-old chicks, feed and sale of broilers including high cost of transportation whereas  total 72.85% farmers also showed about their lack of knowledge of scientific broiler farming including  construction of shed, winter and summer management, feeding and watering. Overall 64.28% farmers  faced the problem regarding incidence of diseases including lack of diseases investigation and monitoring  facilities whereas 45.71% farmers criticized the non-remunerative prices of broilers. Total 27.14% farmers  showed the problem of non-availability and higher costs of labours whereas overall 68.57% farmers were  united with various private companies for contract farming.
Keywords: Adoption; Bottleneck; Broiler farming; Feeding; Management; Production